'Order' and 'civility': Middle-class imaginaries of citizenship before the Syrian uprising. (June 2018) - Anderson, Paul
Are calls for civility necessarily elitist, serving to reproduce existing hierarchies of social and political power? Or, can they work to clear a space in which citizenship can be reimagined and new political demands can emerge? This article explores the contradictory politics of civility in pre-conflict Aleppo. Notions of incivility and disorder allowed Aleppo's commercial middle classes to reimagine what citizenship might mean by expressing discontent with lethargic and repressive systems of government. However, the same language they mobilised to criticise the state also associated civility and order with a specifically bourgeois habitus, which was deployed to preserve existing domains of urban privilege and to entrench the social precedence of urban propertied elites over the dislocated rural poor. Calls for civility may be simultaneously elitist and emancipatory, envisaging new forms of citizenship and public life, while drawing their energy from sources that are implicated in other forms of hierarchy and exclusion. The article considers the implications of this analysis in relation to the outbreak of the Syrian uprising in 2011.